(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In the era of rapidly developing advanced technologies, the development of the social sphere in order to meet the demand of today’s world for qualified and highly experienced personnel is becoming a global problem. The article considers improving the teaching of natural sciences based on a competency-based approach, global problems facing the field of education, the connection of natural sciences with practice, the development of theoretical and fundamental knowledge, and the improvement of acquired knowledge and skills.